1995
DOI: 10.1172/jci117930
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in FBN1 disrupts profibrillin processing and results in isolated skeletal features of the Marfan syndrome.

Abstract: Dermal fibroblasts from a 13-yr-old boy with isolated skeletal features of the Marfan syndrome were used to study fibrillin synthesis and processing. Only one half of the secreted profibrillin was proteolytically processed to fibrillin outside the cell and deposited into the extracellular matrix. Electron microscopic examination of rotary shadowed microfibrils made by the proband's fibroblasts were indistinguishable from control cells. Sequencing of the FBN1 gene revealed a heterozygous C to T transition at nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
6

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 30 publications
1
121
0
6
Order By: Relevance
“…In vitro experiments have demonstrated that Furin/PACE is unable to process profibrillin that has the R2726W mutation, and fibroblasts harbouring this mutation show markedly reduced deposition of fibrillin (Raghunath et al 1999). In vivo, impaired profibrillin processing caused by the R2726W mutation has been identified in one individual with isolated skeletal features of Marfan syndrome, and in six related subjects presenting with high stature (Milewicz et al 1995). This suggests that the availability of fibrillin for microfibrillogenesis is essential for correct skeletal development, and that MFS skeletal features or isolated high stature might develop in the absence of correct enzyme cleavage (Milewicz et al 1995).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In vitro experiments have demonstrated that Furin/PACE is unable to process profibrillin that has the R2726W mutation, and fibroblasts harbouring this mutation show markedly reduced deposition of fibrillin (Raghunath et al 1999). In vivo, impaired profibrillin processing caused by the R2726W mutation has been identified in one individual with isolated skeletal features of Marfan syndrome, and in six related subjects presenting with high stature (Milewicz et al 1995). This suggests that the availability of fibrillin for microfibrillogenesis is essential for correct skeletal development, and that MFS skeletal features or isolated high stature might develop in the absence of correct enzyme cleavage (Milewicz et al 1995).…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that the availability of fibrillin for microfibrillogenesis is essential for correct skeletal development, and that MFS skeletal features or isolated high stature might develop in the absence of correct enzyme cleavage (Milewicz et al 1995). The proband in the study described above (Milewicz et al 1995) was a 13-yearold boy with isolated skeletal features of Marfan syndrome. He was six feet tall (183 cm, more than the 95th centile for his age) with an upper-to-lower segment ratio of 0.89 and with pectus carinatum, scoliosis, arachnodactyly, and pes planus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Moreover, a human fibrillin-1 mutation (Arg 2726 -Trp) which prevents proteolytic processing of the C-terminal domain, has been reported to result in impaired deposition of the product of the affected allele. 19 From a functional perspective, the possible role of fibrillin-1 localization in the neoplastic thyroid cells merits further investigation. The distribution of fibrillin-1 and fibrillin-2 in developing tissues suggests that both proteins are usually, but not exclusively, associated with elastic fibers.…”
Section: Discussionmentioning
confidence: 99%